1999
DOI: 10.1073/pnas.96.26.14955
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ca 2+ entry by polypeptides of the inositol 1,4,5-trisphosphate receptor (IP3R) that bind transient receptor potential (TRP): Evidence for roles of TRP and IP3R in store depletion-activated Ca 2+ entry

Abstract: Homologues ofS timulation of cells that elevates inositol 1,4,5-trisphosphate (IP3) causes the release of Ca 2ϩ from internal stores and its entry from the external milieu (for reviews see refs. 1-3). The release from internal stores occurs through channels formed by IP3 receptors (IP3Rs), and entry is mediated by a set of functionally heterogeneous but ubiquitous channels that are activated by the store depletion event per se. Transient receptor potential (TRP) proteins have been hypothesized to be structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
268
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(286 citation statements)
references
References 42 publications
(38 reference statements)
13
268
2
2
Order By: Relevance
“…4c). 2-APB is a pharmacological substance, commonly used as an InsP3 receptor antagonist (Birnbaumer et al, 2000;Boulay et al, 1999;Wu et al, 2000). These results validated the results of our previous studies conducted with pneumococci.…”
Section: Ca 2+ Flux Mediated By Lactococci Is Pspc-hpigr Dependentsupporting
confidence: 82%
“…4c). 2-APB is a pharmacological substance, commonly used as an InsP3 receptor antagonist (Birnbaumer et al, 2000;Boulay et al, 1999;Wu et al, 2000). These results validated the results of our previous studies conducted with pneumococci.…”
Section: Ca 2+ Flux Mediated By Lactococci Is Pspc-hpigr Dependentsupporting
confidence: 82%
“…A similar mechanism could also be present for TRPM2 considering evidence that inositol 1,4,5-trisphosphate receptors (IP 3 R) can migrate into the nucleus and IP 3 R directly binds to TRPC channels. 32,33 TRPM2 is expressed in many non-cancerous cells, such as brain and peripheral blood cells. 7,8,34 Considering the function of TRPM2 in these cells is to serve as a mediator of oxidative-stress-induced calcium influx (i.e., the channel is at plasma membrane) and thus apoptosis in those tissues, inhibition of TRPM2 may be beneficial in terms of continued survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence from several laboratories showed that IP 3 R coupling with TRPC can trigger Ca 2ϩ entry, the mechanisms responsible for this critical association event are not clear (23,25,34,(61)(62)(63)(64). Models involving chemical and conformation coupling have been suggested (1, 11, 14 -16, 65).…”
Section: Discussionmentioning
confidence: 99%